Sequential sampling of Euschistus heros (Heteroptera: Pentatomidae) in soybean - Souza, Leandro Aparecido de [UNESP]; Barbosa, José Carlos [UNESP]; Jurca Grigolli, José Fernando [UNESP]; Fraga, Diego Felisbino [UNESP]; Moraes, Lilian Cristina [UNESP]; Busoli, Antonio Carlos [UNESP] (Univ Sao Paolo, 2014)
Integrated pest management programs for soybean (Glycine max (L.) Merrill) must be based on efficient sampling plans for estimating the pest population. Based on the spatial distribution of the Neotropical brown stink bug Euschistus heros (Fabricius, 1794) found on soybean, it was possible to construct a sequential sampling plan for the survey of this insect found on soybean. The experiment was carried out during two growing seasons, 2010/2011 and 2011/2012, using the transgenic soybean cultivar M 7908 RR, in plots of 10,000 m(2) subdivided into 100 plots of 100 m(2) (10 m x 10 m). Nymphs > 0.5 cm (4th and 5th instars) plus adults were counted weekly from five drop cloth technique samplings per plot. To evaluate insect dispersion in the area, the following indices were used: variance/mean ratio, Morisita's index, Green's coefficient, the k exponent of the negative binomial distribution, and estimation of the common exponent k (kc). To study probabilistic models to describe the spatial distribution of the insects, adjustments of the Poisson and negative binomial distributions were tested. Two sequential sampling plans for separate fields, one for grain production and the other for seed production, were prepared. The data fitted a negative binomial distribution and a sampling plan was drawn up using the sequential likelihood ratio test (SLRT). The maximum sampling unit number expected for control-related decision making was six in grain production fields, and nine in seed production fields.
Keywords: Neotropical brown stink bug; Sampling method